Academics' perception of quality and the ISO 9000 standards in higher education : a case study of the IIUM - Sheela Nair d/o Gopala Nair (Institute of Education, International Islamic University Malaysia, 2008)
This study examined the concept of quality in higher education from the perspective of the academics at the IIUM, and the extent to which the academics' perceptions of quality were congruent with the quality practices stipulated by the ISO 9000 standards. The study also sought to highlight the underlying factors that formed the basis of the academics' perceptions of quality. The researcher felt that these issues had to be explored in order to understand the academics' response to the university's efforts to use the ISO 9000 certification processes as a visible means to state its commitment to providing quality educational services. The study utilized both the qualitative as well as the quantitative methods of data collection. Qualitative data were collected by carrying out in-depth interviews with academics from the various kulliyyahs. The academics who participated in the interview sessions were carefully selected in order to ensure that the sessions would yield thick, descriptive, and indepth data. To add to the depth and scope of this study, the researcher resorted to a self-developed questionnaire which was administered to the academics of the kulliyyah of Economics and Management Sciences (KENMS), the first kulliyyah to be certified to the ISO 9000 standards. The questionnaire also included six open-ended items which provided the academics with the opportunity to state their views and feelings in their own words.The outcome of the study revealed the fact that the academics in this study had their own notions about what constitutes quality in higher education, based on their own philosophical inclinations and experiences. The results of the study also indicated that the academics did not view the ISO 9000 standards as an appropriate mechanism to enhance the quality of educational services provided by the university. More importantly, the academics did not appreciate the fact that they have been forced to adhere to the requirements of the ISO 9000 certification processes which they feel is irrelevant to academic work.